O Desenvolvimento local sustentável no semi-árido nordestino: um estudo de caso na comunidade de Mirandas, Caraúbas/RN - Falcão, Roberta Borges de Medeiros (2005)
Brazil s semi-arid region is an immense territory characterized by a mosaic of natural environments and human settlements. Inside this multifaceted framework, there are problems that are specific to the region (the water resources situation, for example) while others are more universal (such as the inequality between men and women). The circumstances that give rise to these problems are complex and require a holistic view so that our understanding can go beyond the simple concept that this is a problem region . The semi-arid must be perceived as a viable area in need of a new analysis, taking into account its successes, limitations, challenges and the strategic public policy framework that guarantees its sustainable development. The dissertation analyzes, from a sustainable local development perspective, the experience of the Northeastern Brazil Groundwater Project (PROASNE), carried out from 2001 to 2003, in partnership with the Waters and Sewers Company of Rio Grande do Norte (CAERN) in the rural community of Mirandas, municipality of Caraúbas/RN, situated in the middle of the northeastern Brazil semi-arid region